The Reliability of E-learning at University meanwhile Corona Virus - Nouari , Wafa (Caminos educativos, 2022)
This paper aims to show the effective role of ‘e-learning’ in teaching and learning as well. So, the research problem is based on how the e-learning could contribute to the learning process and develop the learner’s level without a real teacher. Methodologically, this study is working through descriptive and analytical methods since this work is mainly based on descriptions and analyzes of case study that requires defining, explaining, comparing, describing, and interpreting. In addition, the methodological theory we intend to work through is the analytical approach since we will be focusing on e-learning as a global phenomena is multiply increasing due to certain circumstances.